Inhibitive effect of Urginea epigea methanolic extract and silver/zinc oxide nanoparticles on Aspergillus and aflatoxin production - Martha Cebile Jobe; Mulunda Mwanza (PLoS ONE, 2025)
Food crops contaminated with Aspergillus flavus due to aflatoxins can be hazardous for both humans and animals, hence endeavours are being explored to find natural antifungals to combat the contamination and mycotoxin issue. The current study used the agar dilution method to assess the effect of Urginea epigea methanolic extract and biosynthesized silver-zinc oxide nanoparticles on the toxigenic strain of Aspergillus. In the experiment, an aflatoxin-producing strain was used, and potato dextrose agar was diluted with methanolic extract from U. epigea and silver/zinc oxide nanoparticles at concentrations of 0, 6.5, 12, 25, and 50 mg/mL, respectively. Mycelia growth diameters were measured to test inhibitory activity. A significant decrease in fungal growth was observed at different concentrations (P < 0,05) when compared to the control. At 50 mg/mL, the extract of U. epigea significantly reduced the growth of A. flavus by 100%. PCR data shows that the expression of aflD and aflR was significantly downregulated (P < 0.005) by the treatments, with U. epigea having a 50fold decrease when compared to Ag/ZnO nanoparticles. Compared to the controls, Ag/ZnO nanoparticles down-regulated the expression of aflD and aflR in A. flavus by more than 30-fold. However, there was less expression by nanoparticles, as evidenced by the sequence alignment. A. flavus growth and aflatoxin B1 production were both considerably suppressed by U. epigea methanolic extract, through the presence of phytochemicals thus has the potential to be employed as an alternative antifungal agent to control aflatoxigenic fungus. The study recommends investigating and extracting the active compound present in the U. epigea bulb.